Cell-Free Total and Fetal DNA in First Trimester Maternal Serum and Subsequent Development of Preeclampsia - Silver, Robert M.; Myatt, Leslie; Hauth, John C.; Leveno, Kenneth J.; Peaceman, Alan M.; Ramin, Susan M.; Samuels, Philip; Saade, George; Sorokin, Yoram; Clifton, Rebecca G.; Reddy, Uma M. (American Journal of Perinatology, 2017)
Objective The objective of this study was to assess the relationship between first trimester cell-free total and fetal DNA in maternal plasma and the subsequent development of preeclampsia.Study Design Nested case–control study of patients enrolled in the Combined Antioxidant and Preeclampsia Prediction Studies prediction study of 175 women who did and 175 women who did not develop preeclampsia. The predictive values of cell-free total and fetal DNA and the subsequent development of preeclampsia were measured using receiver operating characteristic curves.Results Cell-free total DNA was higher in African American (median; 25–75%; 6.15; 0.14–28.73; p = 0.02) and Hispanic (4.95; 0.20–26.82; p = 0.037) compared with white women (2.33; 0.03–13.10). Levels of cell-free total DNA were also associated with maternal body mass index (BMI) (p = 0.02). Cell-free total DNA levels were similar between women who later developed preeclampsia (3.52; 0.11–25.3) and controls (3.74; 0.12–21.14, p = 0.96).Conclusion There is no significant difference in levels of cell-free total DNA in the first trimester in women who subsequently develop preeclampsia. Levels of cell-free total DNA in the first trimester are increased in African American and Hispanic compared with white women, and levels increase with increasing BMI.
Keywords: preeclampsia; cell-free DNA; placenta; fetal fraction